Flux-controllable and fast state inversion in a Laudau–Zener system of superconducting charge qubit. (1st March 2023) - Yan, Run-Ying; Feng, Zhi-Bo
Abstract: Coherent control of quantum systems in an optimized manner is of significance to information processing and state engineering. In this paper, an effective scheme is proposed for implementing rapid state inversion in a Laudau–Zener (LZ) system of superconducting charge qubit. By linearly adjusting time-dependent gate charge, the system with a given tunneling splitting of energy can be described by the LZ model. By means of the applied flux capable of inducing desired level spacing, qubit state inversion with high probability can be performed in a short time. We further address the criterion to ensure system evolution with negligible non-adiabatic excitation. With the accessible decoherence rates, high-fidelity operations can be obtained numerically. Without adding auxiliary driving, the present strategy could perform the shortcut-like accelerated operation, which paves a promising avenue towards optimized information processing with superconducting qubits.